Genome-wide 5-hydroxymethylcytosine (5hmC) reassigned in Pten-depleted mESCs along neural differentiation - Wang, Zhangting; Miu, Kai-Kei; Chan, See-Wing; Ou, Fanghong; Wai-Nok Law, Patrick; Chan, Wai-Yee (Frontiers in Cell and Developmental Biology, 2022)
DNA methylation and hydroxymethylation have been implicated in the regulatory dynamics of gene expression in normal development and differentiation. 5-Hydroxymethylcytosine (5hmC), created by the ten-eleven translocation (TET) protein-catalyzed oxidation of 5-methylcytosine (5mC), is abundant in the brain, but the genome-wide distribution and impact of 5hmC during diverse neuronal differentiation remain unknown. Here, we used an in vitro model to differentiate mouse embryonic stem cells (mESCs) into ventral midbrain and hindbrain neural progenitors, followed by characterizing global 5hmC distribution using a nano-5hmC-seal approach. The 5hmC pattern was dynamic in promoter, exon, and enhancer regions, associated with gene activation and repression. For example, ventral midbrain markers (Lmx1a, Otx2, and Th) and hindbrain markers (Hoxa1, Zic1, and Tph1) acquire 5hmC and are upregulated during differentiation. Among the differentially expressed genes involved in both midbrain and hindbrain lineage commitment, phosphatase and tensin homolog (Pten) was identified as a key regulator for neuronal development. We confirmed that Pten knockout disrupted the normal differentiation of midbrain/hindbrain neural progenitors, resulting in immature neurons. In addition, 5421 and 4624 differentially hydroxymethylated regions (DhMRs) were identified in the differentiation of Pten−/− mESC into ventral midbrain and hindbrain progenitors, respectively. Gene ontology analysis showed that the majority of these DhMRs were associated with neurogenesis, ectoderm development, and signal transduction. Moreover, further combinational analysis of the 5hmC pattern and transcriptomic profile in the midbrain progenitor cells demonstrated Pten as a toggle to modulate mitochondrial associated pathways. Therefore, our findings elucidated the molecular mechanisms underlying lineage-specific differentiation of pluripotent stem cells to the midbrain/hindbrain progenitors, where Pten participates as one key regulator.